No prediction without prevention: A global qualitative study of attitudes toward using a prediction tool for risk of developing depression during adolescence - Brandon A. Kohrt; Syed Shabab Wahid; Katherine Ottman; Abigail Burgess; Anna Viduani; Thais Martini; Silvia Benetti; Olufisayo Momodu; Jyoti Bohara; Vibha Neupane; Kamal Gautam; Abiodun Adewuya; et al. (Cambridge Prisms: Global Mental Health)
Given the rate of advancement in predictive psychiatry, there is a threat that it outpaces public and professional willingness for use in clinical care and public health. Prediction tools in psychiatry estimate the risk of future development of mental health conditions. Prediction tools used with young populations have the potential to reduce the worldwide burden of depression. However, little is known globally about adolescents’ and other stakeholders’ attitudes toward use of depression prediction tools. To address this, key informant interviews and focus group discussions were conducted in Brazil, Nepal, Nigeria and the United Kingdom with 23 adolescents, 45 parents, 47 teachers, 48 health-care practitioners and 78 other stakeholders (total sample = 241) to assess attitudes toward using a depression prediction risk calculator based on the Identifying Depression Early in Adolescence Risk Score. Three attributes were identified for an acceptable depression prediction tool: it should be understandable, confidential and actionable. Understandability includes depression literacy and differentiating between having a condition versus risk of a condition. Confidentiality concerns are disclosing risk and impeding educational and occupational opportunities. Prediction results must also be actionable through prevention services for high-risk adolescents. Six recommendations are provided to guide research on attitudes and preparedness for implementing prediction tools.